1990
DOI: 10.1128/iai.58.12.3980-3987.1990
|View full text |Cite
|
Sign up to set email alerts
|

Identification of seven surface-exposed Brucella outer membrane proteins by use of monoclonal antibodies: immunogold labeling for electron microscopy and enzyme-linked immunosorbent assay

Abstract: A panel of monoclonal antibodies (MAbs) to seven Brucella outer membrane proteins were characterized. These antibodies were obtained by immunizing mice with sodium dodecyl sulfate-insoluble (SDS-I) fractions, cell walls, or whole bacterial cells of Brucella abortus or B. melitensis. Enzyme-linked immunosorbent assays were used to screen the hybridoma supernatants and to determine their binding at the surface of rough and smooth B. abortus and B. melitensis cells. The outer membrane proteins (OMPs) recognized b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
0
1

Year Published

1992
1992
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(104 citation statements)
references
References 35 publications
(33 reference statements)
9
92
0
1
Order By: Relevance
“…Thus, it is tempting to speculate that the 40to 43-and 20-kDa proteins are relatively more accessible to antibodies than the other three MOMPs (48 to 50, 35 to 36, and 27 to 28 kDa). This is also consistent with the idea that gram-negative bacteria, including V. cholerae, have fewer surface-exposed proteins (5,36,49), probably as a result of a shielding effect of the long LPS 0 side chain. Interestingly, all the anti-MOMP sera showed comparable ELISA titers against in vivo-and in vitro-grown cells of V. cholerae, thereby suggesting no marked differences in the expression or surface exposition of MOMPs in V. cholerae cells grown in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 90%
“…Thus, it is tempting to speculate that the 40to 43-and 20-kDa proteins are relatively more accessible to antibodies than the other three MOMPs (48 to 50, 35 to 36, and 27 to 28 kDa). This is also consistent with the idea that gram-negative bacteria, including V. cholerae, have fewer surface-exposed proteins (5,36,49), probably as a result of a shielding effect of the long LPS 0 side chain. Interestingly, all the anti-MOMP sera showed comparable ELISA titers against in vivo-and in vitro-grown cells of V. cholerae, thereby suggesting no marked differences in the expression or surface exposition of MOMPs in V. cholerae cells grown in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 90%
“…During the analysis of the localization of OM components by IF, Omp25, one of the major Omp of B. abortus (Dubray & Bezard, 1980), was found to have a homogenous distribution [83.7 AE 8.2% (mean AE SD), n = 479 bacteria, five biological replicates] on the cell surface ( Fig 4A, panel 0 h), suggesting that it is continuously produced during the cell cycle like previously reported (Francis et al, 2017). The specificity of the anti-Omp25 mAb (Cloeckaert et al, 1990) was additionally confirmed by IF and Western blot with A Roughness measurements on R-LPS labeled (green) WT and Dgmd cells. AFM images of whole bacteria and of the separated areas (colored squares in first images, 0.4 × 0.4 lm 2 ) are shown.…”
Section: Unipolar Insertion Of Omp25 and Absence Of Long-range Diffussupporting
confidence: 65%
“…This was also found in the rough strain Dgmd, suggesting that the patchy labeling is not an artifact due to the steric hindrance of mAb binding to Omp2b by S-LPS. Labeling with another mAb (A68/25G05/A05) also directed against Omp2b (Cloeckaert et al, 1990) showed the same heterogeneity in localization. We thus wondered whether Omp2b and R-LPS could be co-localized.…”
Section: Clusters Of R-lps Are Co-localizing With the Essential Omp2bmentioning
confidence: 75%
“…After standardizing for total protein content, samples were subjected to electrophoresis on 12% SDS‐PAGE and transferred to Hybond‐C nitrocellulose membranes (Amersham Pharmacia Biotech) by the semi‐dry transfer technique. Immunodetection of proteins was performed with polyclonal anti‐VirB8 (Rouot et al ., 2003) or anti‐FlgE (Fretin et al ., 2005) antisera (diluted 2500 times) and with monoclonal anti‐Omp1 antibody A53 10B2 (Cloeckaert et al ., 1990) (diluted 1000 times) as a loading control. Bound antibodies were detected using chemiluminescence with peroxydase‐conjugated secondary antibodies and the ECL Western blotting reagents RPN2209 as recommended by the manufacturer (Amersham Pharmacia Biotech).…”
Section: Methodsmentioning
confidence: 99%